2016
DOI: 10.3389/fcimb.2015.00105
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Activation of TLR3-Dependent TRIF Signaling Confers Host Defense against Gram-Negative Bacteria in the Intestine

Abstract: Recognition of Gram-negative bacteria by toll-like receptor (TLR)4 induces MyD88 and TRIF mediated responses. We have shown that TRIF-dependent responses play an important role in intestinal defense against Gram-negative enteropathogens. In the current study, we examined underlying mechanisms of how systemic TRIF activation enhances intestinal immune defense against Gram-negative bacteria. First we confirmed that the protective effect of poly I:C against enteric infection of mice with Yersinia enterocolitica w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“…In murine Yersinia enterocolitica infection, systemic administration of poly(I:C) activated NK cells in the mesenteric lymph nodes and induced their IFN-γ expression. Poly(I:C)-induced NK cell activation was mediated by type 1 IFNs and IL-12p40 [36]. In the present study, unlike other pro-inflammatory compounds, IFN-γ concentrations were not positively correlated with bacterial densities (spleen: r s = − 0.37, P = 0.07), and IFN-γ concentrations in the spleen and cerebellum remained high in surviving poly(I:C)-treated mice.…”
Section: Discussioncontrasting
confidence: 70%
“…In murine Yersinia enterocolitica infection, systemic administration of poly(I:C) activated NK cells in the mesenteric lymph nodes and induced their IFN-γ expression. Poly(I:C)-induced NK cell activation was mediated by type 1 IFNs and IL-12p40 [36]. In the present study, unlike other pro-inflammatory compounds, IFN-γ concentrations were not positively correlated with bacterial densities (spleen: r s = − 0.37, P = 0.07), and IFN-γ concentrations in the spleen and cerebellum remained high in surviving poly(I:C)-treated mice.…”
Section: Discussioncontrasting
confidence: 70%
“…Several studies have demonstrated that TRIF-dependent IFNβ production is an important feature of the host-response that aids in the resolution of gram negative bacterial infections (5557). However, gram negative bacteria pathogens such as Yersinia and Klebsiella have evolved an armament of virulence factors to manipulate host-responses and facilitate their pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Protective host defenses mediated specifically by TRIF have been described in response to several gram-negative bacterial pathogens (5557). For instance, pulmonary infection by Klebsiella has been found to become significantly more deadly in TRIF-deficient mice (55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T oll-like receptors are essential components of the immune system and play an important role in infectious and noninfectious disease processes. For example, TLR3 plays a protective role in enteric bacterial infection (1). Bipolar disorder patients exhibit high expression of TLR2 and TLR5 (2).…”
mentioning
confidence: 99%